Pelatihan Desain Grafis Untuk Meningkatkan Kreatifitas Siswa - Lisnawita Lisnawita; Lucky Lhaura Van FC; Musfawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of technological advances now requires the participation of schools in planning technological advances today, and there are positive and negative problems that perceived as one of the negative impacts of technology that felt today using social media that is not good and is misused by students. For this reason, Graphic students need to guided to use the time to increase their creativity so that students can produce more useful work. This service is done by directed/guided demonstration by the speaker and practised directly by the participants. After the training conducted, it can increase students' understanding by 63.73%, and students, express their creative ideas in the form of book covers and business cards